2020
DOI: 10.1016/j.chest.2020.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Noninvasive Assessment of Pulmonary Gas Exchange During Exercise in Hypoxia

Abstract: Validation of a Non-invasive Assessment of Pulmonary Gas Exchange During Exercise in 2 Hypoxia 3 4 Running Head: Non-invasive pulmonary gas exchange in hypoxic exercise 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
4
10
0
Order By: Relevance
“…Pulmonary gas exchange Pulmonary gas exchange efficiency was evaluated and indexed via the O 2 deficit -the difference between the end-tidal and the calculated arterial P O 2 (via pulse oximetry and corrected for the Bohr effect by using the end-tidal P CO 2 ; AGM100, MediPines Corp., Yorba Linda, CA, USA). The O 2 deficit compares well with the traditional ideal alveolararterial P O 2 difference (A − aD O 2 ) calculated from arterial blood gases, and has been validated in a variety of healthy and patient populations (West et al, 2019) and during exercise (Howe et al, 2020)). In the normal healthy lung, there exists regional differences in ventilationperfusion matching, which varies depending on whether the individual is upright (West, 1962) or supine (Wagner et al, 1974).…”
Section: Experimental Measuresmentioning
confidence: 74%
“…Pulmonary gas exchange Pulmonary gas exchange efficiency was evaluated and indexed via the O 2 deficit -the difference between the end-tidal and the calculated arterial P O 2 (via pulse oximetry and corrected for the Bohr effect by using the end-tidal P CO 2 ; AGM100, MediPines Corp., Yorba Linda, CA, USA). The O 2 deficit compares well with the traditional ideal alveolararterial P O 2 difference (A − aD O 2 ) calculated from arterial blood gases, and has been validated in a variety of healthy and patient populations (West et al, 2019) and during exercise (Howe et al, 2020)). In the normal healthy lung, there exists regional differences in ventilationperfusion matching, which varies depending on whether the individual is upright (West, 1962) or supine (Wagner et al, 1974).…”
Section: Experimental Measuresmentioning
confidence: 74%
“…The measurement of oxygen deficit encompasses the effects of low VA/Q and high VA/Q, although the effect of high VA/Q regions on arterial PO 2 is small because of the shape of the O 2 -Hb dissociation curve. The large overlap in the areas of influence of the two methods ( Figure 2 ) means that the two measurements would be expected to be highly correlated, albeit not the same, and this was demonstrated with a strong correlation between measures of A-aDO 2 and OD ( West et al, 2018c ; Howe et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also demonstrated the validity of the non-invasive approach to measure a gas exchange deficit. A direct comparison between OD and arterial blood gas (ABG) was performed in 25 normal subjects during hypoxic exercise, showing a correlation between OD and A-aDO 2 with an r 2 =0.71, and with a small bias between the two, with OD being on average 5.2±5.0mmHg higher than A-aDO 2 ( Howe et al, 2020 ). The non-invasive nature of the measurement serves to enable measurements in conditions in where it would be challenging to perform ABGs, and in particular, serial ABGs.…”
Section: Oxygen Deficit In Normal Subjectsmentioning
confidence: 99%
“…A-aDO 2 and RI can evaluate the pulmonary ventilation function reliably. In addition, A-aDO 2 is a sensitive indicator of pulmonary diffusion function and pulmonary gas exchange e ciency in the early stage of ventilation insu ciency [24,25]. OI indicates the lung ventilation function and oxygen utilization, is directly proportional to lung function.…”
Section: Discussionmentioning
confidence: 99%